2002
DOI: 10.1046/j.1365-2109.2002.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent pharmacokinetics and tissue distribution of oxolinic acid in sea bass, Dicentrarchus labrax L., after a single intravascular injection

Abstract: The pharmacokinetics and tissue distribution of oxolinic acid following an intravascular administration (15 mg kg À1 fish) were determined in sea bass, Dicentrarchus labrax L. (110 g), at 13 8C and 22 8C water temperature. The kinetic profile of the drug was found to be temperature dependent, with increased temperature having a greater effect on distribution after equilibrium and the elimination phase than on the distribution process. The distibution half-life of oxolinic acid was 1.15 and 2.76 h at 22 8C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
6
26
2
Order By: Relevance
“…This finding is in agreement with the results for oxolinic acid in catfish (Kleinow et al. 1994), but contrasts with the results of Rigos et al. (2002a,b).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This finding is in agreement with the results for oxolinic acid in catfish (Kleinow et al. 1994), but contrasts with the results of Rigos et al. (2002a,b).…”
Section: Discussionsupporting
confidence: 78%
“…1992), channel catfish (Kleinow et al. 1994) and sea bass (Rigos et al. 2002b), for oxytetracycline in sea bass (Rigos et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding values for FLU (18-24°C) and SARA (18-25°C) for muscle and skin of the same species were found to be 22 and 18-33 h (Tyrpenou et al, 2003a,b). Overall, the elimination of quinolones appears to be rapid in euryhaline fish species and highly temperaturedependent (Rigos et al, 2002b;Tyrpenou et al, 2003a,b). Consequently, daily dosing of quinolone drugs should be mandatory, especially at higher water temperatures, to maintain maximum tissue drug concentrations in euryhaline fish.…”
Section: (Fluoro)quinolonesmentioning
confidence: 95%
“…of Scophthalmus maximus ( n =5), at 16°C and 10°C water temperatures previously reported that a temperature increment of 1°C corresponds to a 10% increase in the metabolic and excretory rates of fi sh (Rigos et al, 2002a). Rigos et al (2002b) also demonstrated the effect of temperature on the t 1/2 β of oxolinic acid in sea bass plasma, and similar profi le was found in gilthead seabream and crucian carp (Tyrpenou et al, 2003;Ding et al, 2006). Similar to Liang et al (2010), the t 1/2 β of enrofl oxacin after oral administration was 137 h at 10°C and 99 h at 16°C, but differed from that of 25 h reported for sea bass at 15°C (Intorre et al, 2000), 42.1 h for koi carp at 27-28°C (Udomkusonsri et al, 2007), or 161.10 h for European eel at 23-25°C .…”
Section: The Comparative Pharmacokinetics Of Enrofl Oxacinmentioning
confidence: 99%